2008
DOI: 10.1002/art.23406
|View full text |Cite
|
Sign up to set email alerts
|

T cell polarization identifies distinct clinical phenotypes in scleroderma lung disease

Abstract: Objective. Lung involvement is the leading cause of morbidity and mortality in systemic sclerosis (SSc; scleroderma), and interstitial lung disease (ILD) is the most common pulmonary manifestation. An abnormal profibrotic Th2/Tc2-polarized T cell response is postulated to mediate tissue damage and fibrosis. The aim of this study was to investigate whether a polarized T cell phenotype in SSc is associated with lung disease or other clinical manifestations of SSc.Methods. Circulating T cells were characterized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 35 publications
(33 reference statements)
1
43
0
3
Order By: Relevance
“…Likewise, several studies have shown that T cells from affected sites such as skin21 22 and bronchoalveolar lavage fluid23 24 from patients with SSc have higher Th2-type cytokines. More recently, the existence of a skewed Th2 response in SSc was further substantiated by a study from Boin et al , in which specific T-cell surface markers were analysed displaying a Th2 phenotype 25. The pathways that underlie such a Th2 skewing have thus far not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, several studies have shown that T cells from affected sites such as skin21 22 and bronchoalveolar lavage fluid23 24 from patients with SSc have higher Th2-type cytokines. More recently, the existence of a skewed Th2 response in SSc was further substantiated by a study from Boin et al , in which specific T-cell surface markers were analysed displaying a Th2 phenotype 25. The pathways that underlie such a Th2 skewing have thus far not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the initiating event or trigger, the extensive innate and cellular immune abnormalities in SSc [35,6267] result in exaggerated Th2 response driving the increased expression and production of numerous and potent profibrotic cytokines and growth factors. Besides cellular immunity alterations, abnormal humoral immunity leading to the production of numerous autoantibodies is a nearly universal manifestation of SSc.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Activated fibroblasts differentiating to myofibroblasts secrete excessive amounts of hyaluronic acid, fibronectin, proteoglycans and interstitial collagens, that remodel and destroy normal tissue architecture (Wynn 2007). In particular, fibroblast collagen production is enhanced by T helper type 2 lymphocytes (Th2) cytokines, including interleukin (IL)-4 and IL-13 and inhibited by cytokines produced by Th1 cells (e.g., interferon (IFN)-g and tumor necrosis factor (TNF)-a) (Aliprantis et al 2007;Bhogal et al 2005;Lafyatis 2006;Boin et al 2008). gd T cells may also influence the fibrotic process after exposure to chronic inflammatory stimuli, since it has recently been found that: (1) mice lacking the gd T cell subset (T cell receptor (TCR) d À/À ) have enhanced bleomycin-induced lung fibrosis, (2) gd T cell depletion augments pulmonary fibrosis in C57BL/6 mice repetitively exposed to B. subtilis and (3) adriamycin-induced interstitial fibrosis of the kidney is exacerbated in the absence of gd T cells (Braun et al 2008;Simonian et al 2006;Wu et al 2007).…”
Section: Introductionmentioning
confidence: 99%